DOES KAMCHATKA BELONG TO NORTH AMERICA? AN EXTRUDING OKHOTSK BLOCK SUGGESTED BY COASTAL NEOTECTONICS OF THE OZERNOI PENINSULA, KAMCHATKA, RUSSIA - Pedoja K.; Bourgeois J.; Higman B.; Pinegina T. (My University, 2006)
This paper addresses one part of an outstanding tectonic problem regarding the nature of the plate boundary between Eurasia and North America in northeastern Russia. In this region, the northwestern corner of the Pacific plate interacts either simply with the North American plate, or more complexly with one or more blocks independent of North America. North of this corner, evidence of uplift, tilting, and convergence contradicts the prevailing, simpler model. On the Ozernoi Peninsula, ~150 km north of the subducting Pacific plate, marine terraces indicate uplift rates of 0.1 to 0.3 mm/yr, with faster rates to the east. Historic and paleoseismic records provide evidence for recurring tsunamigenic, thrust earthquakes offshore of the Ozernoi Peninsula, the most recent a Mw 7.7 earthquake in 1969. A multiplate model where an eastward-moving Okhotsk block, including most of Kamchatka, is converging with a clockwise-rotating Bering block better explains these observations than does the unbroken North American plate model. © 2006 Geological Society of America.
Keywords: BERING SEA; KAMCHATKA; NEOTECTONICS; OKHOTSK; PLATE TECTONICS; QUATERNARY MARINE TERRACES